Measuring Carbon for Urban Development Planning - Beattie, Colin; Bunning, Jessica; Stewart, Joanne; Newman, Peter; Anda, Martin (The International Journal of Climate Change: Impacts and Responses, 2012)
This paper examines a framework for calculating carbon dioxide equivalent (CO2-e) emissions in urban developments, including emissions inherent in: materials, construction, operation, transport, water, and waste processes over the life cycle of a development. The paper takes a holistic approach to urban design, to include not only the CO2-e emissions inherent in the individual buildings but also in the infrastructure and service provision of the community as a whole metabolic system. A range of carbon assessment tools is examined to assess their capacity for measuring CO2-e emissions in terms of this framework. The tools are reviewed for their applicability to four case studies in Western Australia: Peri-urban development (greenfield), Urban redevelopment (brownfield), Mining camps, and Indigenous communities, which demonstrate the type of settlement patterns that carbon assessment tools must respond to. The case studies are also indicative of the challenges facing other urban developments around the world in cutting CO2-e emissions and enhancing sustainability. The results of the study show that two tools are currently available that can measure and model carbon emissions and carbon consequences of variations of design in urban developments. The tools CCAPPrecint and e-Tool are highlighted in this paper as outstanding examples.